GlycoPep Grader: A web-based utility for assigning the composition of N-linked glycopeptides - Woodin, Carrie L. (2012)
GlycoPep Grader (GPG) is a freely-available software tool designed to accelerate the process of accurately determining glycopeptide composition from tandem mass spectrometric data. GPG relies on the identification of unique dissociation patterns shown for high mannose, hybrid, and complex N-linked glycoprotein types, including patterns specific to those structures containing fucose or sialic acid residues. The novel GPG scoring algorithm scores potential candidate compositions of the same nominal mass against MS/MS data through evaluation of the Y(1) ion and other peptide-containing product ions, across multiple charge states, when applicable. In addition to evaluating the peptide portions of a given glycopeptide, the GPG algorithm predicts and scores product ions that result from unique neutral losses of terminal glycans. GPG has been applied to a variety of glycoproteins, including RNase B, asialofetuin and transferrin, and the HIV envelope glycoprotein, CON-S gp140 CFI. The GPG software is implemented predominantly in PostgreSQL, with PHP as the presentation tier, and is publically accessible online. Thus far, the algorithm has identified the correct compositional assignment from multiple candidate N-glycopeptides in all tests performed.